On the Ritt order of a certain class of functions - R. Parvatham; J. Thangamani (International Journal of Mathematics and Mathematical Sciences)
The authors introduce the notions of Ritt order and lower order to functions defined by the series ∑1∞fn(s)exp(−λns) where (λn) is a D-sequence and fn(s) are entire functions of bounded index.